Analisis Disiplin Kerja PNS di Dinas Ketenagakerjaan Kabupaten Supiori - Iriawan, Hermanu; Tandi , Junita Garianti (Universitas 17 Agustus 1945 Semarang, 2025)
Optimizing public services is providing professional and quality services that have positive implications for community satisfaction. This study aims to find out the Work Discipline of Civil Servants at the Manpower Office of Supiori Regency. The type of research carried out is qualitative research. Data collection techniques are carried out through observation, interviews and literature studies. Furthermore, the data analysis technique used is a qualitative data analysis technique. The results of the research show that the indicators seen based on time discipline, responsibility discipline, and regulatory discipline have gone well, which in general employees at the Manpower Office of Supiori Regency show a good level of compliance with the rules and regulations that have been set.